2014
DOI: 10.1097/qai.0000000000000028
|View full text |Cite
|
Sign up to set email alerts
|

Jurisdiction Level Differences in HIV Diagnosis, Retention in Care, and Viral Suppression in the United States

Abstract: Using data from the National HIV Surveillance System, we determined the number of persons diagnosed with HIV and the percentages of persons linked to care, retained in care, and virally suppressed across 19 jurisdictions with complete reporting of CD4 and viral load test results. Reports from these jurisdictions represent 37% of persons diagnosed with HIV infection in the United States in 2011. Although 80% of persons diagnosed in 2011 were linked to HIV medical care within 3 months of diagnosis, half of all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 10 publications
1
60
1
Order By: Relevance
“…Further, those with a high school degree/GED or less had lower levels of interest and participating in masturbation (P < .05). Males with CD4 counts <200 cells/mm 3 had lower overall sexual function, interest, desired, and arousal compared to those with CD4 counts 200 cells/mm 3 (P < .05). Males with unsuppressed viral loads also appeared to have lower sexual function related to interest, desire, and arousal in comparison to those with suppressed viral loads (P < .05).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Further, those with a high school degree/GED or less had lower levels of interest and participating in masturbation (P < .05). Males with CD4 counts <200 cells/mm 3 had lower overall sexual function, interest, desired, and arousal compared to those with CD4 counts 200 cells/mm 3 (P < .05). Males with unsuppressed viral loads also appeared to have lower sexual function related to interest, desire, and arousal in comparison to those with suppressed viral loads (P < .05).…”
Section: Resultsmentioning
confidence: 95%
“…HIV viral loads were dichotomized (<400 copies/mL and >400 copies/mL) as was the standard test results at the time of data collection. CD4 counts were dichotomized as well (<200 cells/mm 3 and >200 cells/mm 3 ). Descriptive analyses were conducted to define the overall sample.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…25 It has also been demonstrated that engagement and retention in care vary widely by state and location in the United States, underscoring the need to evaluate geographic and localized gaps in the continuum of care. 26 Prior studies have shown that lack of continuous engagement in care is associated with noninitiation of ARV. 8,27 In contrast, the number of visits in the past year was not significantly associated with ARV prescription in our study.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The continued and increasing need for high-quality, usable surveillance data was underscored by the release of the 2010 National HIV/AIDS Strategy (NHAS), which calls for a coordinated national response to HIV in the United States. 7 To maximize the ability to monitor trends in HIV in the U.S. and progress toward meeting prevention goals, the Centers for Disease Control and Prevention (CDC) has developed a comprehensive National HIV Surveillance System (NHSS) that guides data collection and reporting.…”
mentioning
confidence: 99%